Pulmonary Thromboembolism caused by Traumatic Thrombosis - Bermúdez, Jorge; Delgado, Bolívar; Heguy, Pedro (Cirugía del Uruguay, 1981)
Report on a case of grave recurrent thromboembolism, secondary to traumatic thrombosis of subclavian vein.